2013
DOI: 10.1016/j.ygeno.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of copy number variation by Illumina next generation sequencing is comparable in performance to oligonucleotide array comparative genomic hybridisation

Abstract: Array comparative genomic hybridisation (aCGH) profiling is currently the gold standard for genetic diagnosis of copy number. Next generation sequencing technologies provide an alternative and adaptable method of detecting copy number by comparing the number of sequence reads in non-overlapping windows between patient and control samples. Detection of copy number using the BlueGnome 8×60k oligonucleotide aCGH platform was compared with low resolution next generation sequencing using the Illumina GAIIx on 39 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…These findings are in line with previous studies reporting associations between 8p loss/LOH with adverse tumor phenotype [25][26][27][28][29] and poor clinical outcome. 25,27,29,31 Studies that could find associations of 8p deletions with tumor progression had involved remarkably small cohorts of 40, 35 44, 36 46, 33 52,38 55, 39 60, 14 61, 32 76 34 and 105 37 patients. The ability to detect a clinical utility of 8p deletion measurement in small cohorts is obviously caused by the high rate of positive cases (almost 50%) and a particularly strong prognostic impact of this feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with previous studies reporting associations between 8p loss/LOH with adverse tumor phenotype [25][26][27][28][29] and poor clinical outcome. 25,27,29,31 Studies that could find associations of 8p deletions with tumor progression had involved remarkably small cohorts of 40, 35 44, 36 46, 33 52,38 55, 39 60, 14 61, 32 76 34 and 105 37 patients. The ability to detect a clinical utility of 8p deletion measurement in small cohorts is obviously caused by the high rate of positive cases (almost 50%) and a particularly strong prognostic impact of this feature.…”
Section: Discussionmentioning
confidence: 99%
“…The strong prognostic impact of 8p deletions makes it very likely, that future prognostic breast cancer tests will include 8p deletion measurement. Given that future next generation sequencing methods may allow for 8p deletion measurement with a comparable accuracy than FISH, 61 such an analysis may be integrated in a multi-parametrical NGS-based breast cancer tests.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐coverage whole genome sequencing is a reliable alternative to array comparative genomic hybridization for detecting large (>40 kb) structural variations that is comparable in cost (Hayes et al. 2013). In this study, CNVseq of an affected individual from Family 2 revealed a large duplication spanning FAM20A .…”
Section: Discussionmentioning
confidence: 99%
“…The detection windows may be evenly distributed across the genome with a fixed window size, or, as array comparative genomic hybridization (aCGH) profiling is currently the gold standard for genetic diagnosis of CNVs [26], the partitioning of the genome may be based on the chromosomal coordinates of the microarray probes. This approach additionally allows direct comparison of both methods [27]. In the case of targeted sequencing (e.g., exomes, gene panels), the chromosomal coordinates of either the region of interest or the baits used for enrichment are preferential limiters of detection windows.…”
Section: Copy Number Variations (Cnvs)mentioning
confidence: 99%